INFLUENCE OF SUBCCRITICAL WATER EXTRACTION PARAMETERSON THE EFFICIENCY OF PROTEIN RECOVERY FROM SOYBEAN MEAL - SUKMANOV, Valeriy; KOVALCHUK, Olena (Herald of Khmelnytskyi National University. Technical sciences, 2022)
This work is devoted to the study of the extraction process of protein from soybean meal with subcritical water. The aim of the study is to determine the influence of parameters (temperature: , extraction duration: (), hydromodulus: ) of the subcritical water extraction process on the protein content in the dry matter of soybean meal extract and their rational values. To determine the rational parameters of the extraction process, an empirical research method was applied using an orthogonal compositional plan of the 2-nd order for a fractional-factorial experiment . Samples of extracts were obtained on a laboratory setup based on a high pressure reactor. In the obtained samples, the total protein content was determined by the method of catalytic oxidation with chemiluminescent detection. On the basis of the obtained results, a quadratic interpolation model was constructed that relates the total protein content in the dry matter of the extract with the extraction parameters. The analysis of the constructed model made it possible to establish the optimal extraction parameters: temperature , extraction duration . The yield of protein to the dry matter of the extract at optimal values of temperature and duration of the process monotonically increases with an increase in the hydromodulus and reaches a maximum at the hydromodulus . The results obtained can be used to improve the technology for obtaining soy protein concentrate and isolate using the subcritical water extraction method. Due to the environmental friendliness of this extraction technology, the resulting extracts can be directly used to improve the nutritional value of various food products.